Primary School Students’ Reading Interest: What Are the Determining Factors? - Karinta Utami; Sima Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study's objectives were to measure students' interest in reading at Tasikmalaya City's Mangkubumi Elementary School and examine how the GLS was being used. Reading interest is an important skill to learn because reading is a habit that every child needs to develop from an early age in order to succeed academically. This study combined a quantitative technique with a descriptive methodology consist 45 students from the school took part in the study. A questionnaire with five indicators on a student's interest in reading and interviews with literacy-teacher were the study tools employed. The data were examined using a descriptive data analysis approach. The results showed that there were two indications with low scores: (1) the habit of supporting reading activities and (2) the desire to read. In addition, two indicators—the enjoyment of reading and interest in books—have ordinary values, while one indicator—the urge to read books—has a high value. The findings show that while respondents are already aware of the value of reading, they are not being encouraged to read at school or at home, which may be influencing their desire and interest in reading activities. This research is beneficial to the advancement of knowledge, particularly in the field of literacy in primary education.